HOW FAR do WE GET USING MACHINE LEARNING BLACK-BOXES? - Rocha, Anderson; Papa, João Paulo [UNESP]; Meira, Luis A. A. (World Scientific Publ Co Pte Ltd, 2012)
With several good research groups actively working in machine learning (ML) approaches, we have now the concept of self-containing machine learning solutions that oftentimes work out-of-the-box leading to the concept of ML black-boxes. Although it is important to have such black-boxes helping researchers to deal with several problems nowadays, it comes with an inherent problem increasingly more evident: we have observed that researchers and students are progressively relying on ML black-boxes and, usually, achieving results without knowing the machinery of the classifiers. In this regard, this paper discusses the use of machine learning black-boxes and poses the question of how far we can get using these out-of-the-box solutions instead of going deeper into the machinery of the classifiers. The paper focuses on three aspects of classifiers: (1) the way they compare examples in the feature space; (2) the impact of using features with variable dimensionality; and (3) the impact of using binary classifiers to solve a multi-class problem. We show how knowledge about the classifier's machinery can improve the results way beyond out-of-the-box machine learning solutions.
Keywords: Machine learning black-boxes; binary to multi-class classifiers; support vector machines; optimum-path forest; visual words; K-nearest neighbors